1997
DOI: 10.2307/1521597
|View full text |Cite
|
Sign up to set email alerts
|

Nest Distance Mediates the Costs of Coloniality in Eared Grebes

Abstract: We examined the behaviors and reproductive characteristics of 4 Eared Grebe (Podiceps nigricollis) colonies located at the Malheur National Wildlife Refuge in eastern Oregon that varied in nesting density. In 1993, we studied 2 colonies found on 2 different lakes, whereas in 1994 we conducted a within-lake comparison of 2 subcolonies. During both years, nearest neighbor distances differed significantly between the colonies investigated. Breeding pairs were significantly more aggressive at those colonies with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Vegetation such as algae, dead cattail (Typha spp. ), cottonwood (Populus deltoides)/willow (Salix amygdaloides, S. interior), common bladderwort (Utricularia vulgaris), coontail (Ceratophyllum demersum), sago pondweed, goosefoot (Chenopodium rubrum), or hardstem bulrush are used as nest material (Bryant 1983, See et al 1992, Boe 1993, Hill et al 1997. Nests may be anchored to emergent plants such as hardstem bulrush, alkali bulrush (Scirpus maritimus), sprangletop (Scolochloa festucacea), and golden dock (Rumex maritimus), or built on dense, floating mats of submergent vegetation or algae (Friley and Hendrickson 1937, Stewart 1975, See et al 1992, Boe 1993.…”
Section: Suitable Habitatmentioning
confidence: 99%
See 4 more Smart Citations
“…Vegetation such as algae, dead cattail (Typha spp. ), cottonwood (Populus deltoides)/willow (Salix amygdaloides, S. interior), common bladderwort (Utricularia vulgaris), coontail (Ceratophyllum demersum), sago pondweed, goosefoot (Chenopodium rubrum), or hardstem bulrush are used as nest material (Bryant 1983, See et al 1992, Boe 1993, Hill et al 1997. Nests may be anchored to emergent plants such as hardstem bulrush, alkali bulrush (Scirpus maritimus), sprangletop (Scolochloa festucacea), and golden dock (Rumex maritimus), or built on dense, floating mats of submergent vegetation or algae (Friley and Hendrickson 1937, Stewart 1975, See et al 1992, Boe 1993.…”
Section: Suitable Habitatmentioning
confidence: 99%
“…Distances between nests within a colony have been reported as 0 to 9.5 m, and depend on habitat conditions (Job 1902, Friley and Hendrickson 1937, McAllister 1958, Buresh 1971, Ray and Kruse 1989, Lyon and Everding 1996, Hill et al 1997. Hill et al (1997) reported that nests in a low-density colony were farther apart (3.3 versus 1.4 m, respectively) than in a high-density colony (numbers of nests within low-and high-density colonies were not given). Depredation rate was higher in the low-density colony than in the high-density colony.…”
Section: Suitable Habitatmentioning
confidence: 99%
See 3 more Smart Citations